Teaching Linear Control Systems:A Core Course in Electrical and Electronics Engineering - Kittur, Javeed (Journal of Engineering Education Transformations, 2016)
This paper presents the experience in teaching the course Linear Control Systems in Electrical and Electronics Engineering curriculum. This course is offered to third year engineering students. Students who pursue a degree in Electrical and Electronics Engineering are required to complete a laboratory course in the same semester. The motivation for offering this course is to make the students aware regarding the importance of control systems, controller design aspects and verification of designed systems through simulation. In order to have a system function as per the requirement, the understanding of control systems engineering is very essential. This paper presents the experience of teaching linear control systems course of an instructor for the first time with the incorporation of peer learning; Think - Pair - Share activity and personal mentoring of students. The students’ performance scores of different tests are presented. Students’ feedback is also included which clearly shows that the instructor has put efforts in doing justice in teaching this course.